Menjelajahi persimpangan revolusi: Bagaimana Blockchain dan IoT berpadu untuk mengubah dunia - Putri, Sheila Apriliani (Maliki Interdisciplinary Journal, 2024)
The aim of writing this article is to determine the role of Blockchain and the Internet of Things (IoT) in changing the way humans interact and driving digital transformation throughout the world. This article will delve into the world’s digital transformation and explore how blockchain and IoT can be combined, IoT connects billions of physical devices to the internet enabling unprecedented real-time data collection and exchange. On the other hand, Blockchain provides a secure and decentralized platform for managing data and ensuring integrity and transparency. The powerful combination of IoT and Blockchain opens up revolutionary opportunities in various sectors and brings rapid progress in life. The combination of these two technologies brings many benefits in the fields of manufacturing, health care, finance and so on. However, on the other hand, several blockchain and IoT applications have quite serious challenges related to security, privacy, interoperability, complexity and cost. By overcoming these challenges and taking advantage of the opportunities offered, we can build a future that is more efficient, safe and transparent for all groups and ready to face the industrial revolution 5.0 or even revolution 7.0 in the future.